Investigating depression among breast cancer patients - Nur Aziera, binti Wahid (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Breast cancer patients are more likely to experience depression during or after cancer. This open study examined four respondents using Beck Depression Inventory as well as interviews to investigate depression among breast cancer patients. The result of the study showed that respondents were having depression after diagnosed with breast cancer and having emotional, cognitive, behaviour and physical changes symptoms. Findings from the study suggested reducing depression by taking psychological treatment, support from beloved one and taking medicines regularly.